Rare bird documentation form for Greater Scaup at Port Neal, 1982 - Schaufenbuel, Joseph P.et al (1982)
Rare bird documentation form for two Greater Scaups at Port Neal in Woodbury County, IA on June 6, 1982. Epson - sheet feed